Improving Fifth-Grade Elementary School Students’ Science Problem-Solving Skills through the Do–Talk–Record Learning Model - Kadek Erna Lestari; I Gusti Ayu Tri Agustiana; Rendy Setyowahyudi, M.Pd. (Indonesian Journal of Instruction, 2026)
Developments in 21st-century learning require the implementation of strategies capable of developing students’ critical thinking and problem-solving skills. However, science education in elementary schools is still dominated by conventional approaches, resulting in students’ problem-solving skills not developing optimally. This study aims to analyze the improvement in students’ science problem-solving skills through the implementation of the Do Talk Record learning method. This study employs an experimental design with a posttest control group. The research subjects consisted of an experimental group that received Do Talk Record instruction and a control group that followed conventional instruction. Data were collected through a validated essay-based problem-solving test and analyzed using descriptive and inferential statistical techniques, including tests of normality, homogeneity, and differences in means. The results indicate that the problem-solving skills of students in the experimental group were higher than those in the control group. These findings suggest that the Do Talk Record learning method is effective in enhancing students’ ability to plan, implement, and evaluate problem-solving strategies, as well as to connect concepts with real-world phenomena. The conclusion of this study confirms that the Do Talk Record learning method contributes positively to the development of students’ problem-solving skills. The implications of this study suggest that the implementation of innovative learning models can support the strengthening of critical thinking skills, problem-solving, and 21st-century competencies in science education at the elementary school level.